Strengthening reading skills through enriched instructional activities for grade three fast learners - Acuña, Kelly P. 1941- (Quezon City College of Education, University of the Philippines Diliman, 1969)
The objective of the study is the strengthening of reading skills like word perception skills, comprehension skills and basic study skills through enriched instructional activities for grade three fast learners. Reading activities for strengthening reading abilities are also suggested so that parents, as well as teachers of grade three fast learners will be guided in developing the children's higher level of reading skills. The study used the integrative approach.
"March, 1969."
Thesis (Master of Arts in Teaching - Special Education : Mental Giftedness)--University of the Philippines, Diliman.
Keywords: Reading (Elementary) -- Philippines; Gifted children -- Education (Elementary) -- Philippines; Activity programs in education -- Philippines